When citizens talk about politics - Saunders, Clare 1975-; Klandermans, Bert 1944- (Routledge, 2020)
This book offers novel insights into the way in which people talk about politics across various countries. Drawing on focus groups research in nine countries, including mature' democracies, post-communist new' democracies and post-authoritarian new' democracies, it offers comparative reflection on how talk about political activity is shaped by peoples' perceptions of specific opportunities to participate, the issues that concern them and the broader political environment. It thus examines citizens' views of major issues and political grievances in their own words and helps to shed new light on reasons for engagement in political acts, whether through electoral or protest channels, or political disengagement
Keywords: Political participation; Public opinion; Öffentliche Meinung; Politische Meinungsäußerung; Politische Kommunikation; Politische Einstellung; Aufsatzsammlung